2018
DOI: 10.1007/s12094-018-1942-0
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial chemoembolization with raltitrexed-based or floxuridine-based chemotherapy for unresectable colorectal cancer liver metastasis

Abstract: Purpose To evaluate and compare the efficiency and safety of raltitrexed-or floxuridine (FUDR)-based transarterial chemoembolization (TACE) in patients with unresectable colorectal cancer liver metastasis (CRCLM). Methods We conducted a retrospective analysis of 81 patients with unresectable CRCLM who failed systemic chemotherapy and were treated with TACE in our department from Oct 2014 to Oct 2017. Of these, 61 patients received TACE using raltitrexed, oxaliplatin, and pirarubicin (raltitrexed group), and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…In accordance with previous reports, our results also showed that targeted therapy served as an independent prognostic factor for both PFS and OS, while TACE, as a regular means of local treatment, was an independent prognostic factor for PFS 8,23,35. Our results also showed that patients with unresectable CLLMs would benefit from systemic therapy first mode rather than primary lesion resected mode in the overall survival, which is consistent with previous reports 36.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with previous reports, our results also showed that targeted therapy served as an independent prognostic factor for both PFS and OS, while TACE, as a regular means of local treatment, was an independent prognostic factor for PFS 8,23,35. Our results also showed that patients with unresectable CLLMs would benefit from systemic therapy first mode rather than primary lesion resected mode in the overall survival, which is consistent with previous reports 36.…”
Section: Discussionsupporting
confidence: 93%
“…Inhibition of TS can lead to DNA breakage and apoptosis 16 . Raltitrexed is a direct and specific TS inhibitor that can enhance the inhibition ability of TS and prolong the inhibition time 17 .…”
Section: Resultsmentioning
confidence: 99%
“…With respect to third-line locoregional therapy for patients with unresectable CRCLM, the present study can be compared to two studies of raltitrexed-based TACE (Guo et al 2017;Wei et al 2019). In the Fudan University Shanghai Cancer Center/Xintai Taishan Medical University study (Wei et al 2019), a median OS of 14 months (PFS of 2.1 months) was reported for raltitrexed (4 mg) combined with oxaliplatin (100 mg) and pirarubicin (60 mg), whereas a median OS of 20.6 (PFS of 4.9 months) was reported in the Peking University Cancer Hospital study (Guo et al 2017) for epirubicin (40 mg plus spongostan particles and iodized oil/lipiodol), followed by 48 h HAI with raltitrexed (3 mg/m 2 ) combined with oxaliplatin (85 mg/m 2 ) and 5-fluorouracil (2000 mg/ m 2 ). The small-sample size (18 patients) in the latter study and failure to report prior first-and second-line systemic chemotherapeutic regimens in both studies, however, limit further discussion of the impressive 20.6-month OS in Peking University Cancer Hospital study (Guo et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Loco-regional chemoembolization (TACE) (Fiorentini et al 2017b(Fiorentini et al ,2018Guo et al 2017;Wei et al 2019) and hepatic artery infusion (HAI) are considered for the third-line therapy in unresectable CRCLM, with the latter indicated for elderly patients with poor performance status and those who refuse surgery or systemic chemotherapy or progress following systemic chemotherapy or to prolong intervals between cycles of systemic chemotherapy (Fiorentini et al 2017a). Risks associated with HAI include treatable catheter and/or port/pump placement complications, life-threatening biliary sclerosis, hepatotoxicity, and/or systemic toxicity (Kingham et al 2010), which can be reduced by chemo-filtration (Fiorentini et al 2004a).…”
Section: Introductionmentioning
confidence: 99%